Research on Design Indicators for Graded Crushed Stone Mixture Based on Vibration Molding Method - Li-biao Chen; Er-hu Yan; Jian Xu; Tao Ma; Jun-cheng Zeng; Yan Gong (Advances in Materials Science and Engineering)
The asphalt pavement easily shows the diseases like cracking, rutting, and structural water damage during the early service life in Fujian province for the complex effects of very high temperature, easily rainy climatic condition, and high-frequency heavy loading. However, the corresponding studies and strategies are still rare. Herein, in order to study the relationship of compaction methods on the stress-strain characteristics and shear strength of graded crushed stone mixtures, 11 kinds of typical graded crushed stone mixtures, which were taken from the five different expressways under construction in Fujian Province, were molded by both the modified vibration compaction and modified Proctor compaction. The results indicate that the modified vibration molding method matches much better with the compaction of practical projects and can be used to evaluate the performance of graded crushed stone mixtures. Further, the performance indexes got by the modified vibration compaction and the modified Proctor compaction have strong correlations. Therefore, based on the modified vibration compaction, the guidelines for standardized mix design of graded crushed stone mixture in Fujian province are proposed: the resilient modulus of 300 MPa and the deformation rate of 10–8 in the dynamic triaxial test are used as the performance indicators of the bearing capacity and the antideformation ability; the shear strength of 400 kPa in the static triaxial test is used as the performance indicators of the shear failure resistance. Besides, most limestone mixtures perform well and have the advantages of good resistance to permanent deformation and shear resistance.